Transforming growth factor β1-mediated functional inhibition of mesenchymal stromal cells in myelodysplastic syndromes and acute myeloid leukemia - Stefanie Geyh; Manuel Rodríguez-Paredes; Paul Jäger; Annemarie Koch; Felix Bormann; Julian Gutekunst; Christoph Zilkens; Ulrich Germing; Guido Kobbe; Frank Lyko; Rainer Haas; Thomas Schroeder (Haematologica, 2018)
Mesenchymal stromal cells are involved in the pathogenesis of myelodysplastic syndromes and acute myeloid leukemia, but the underlying mechanisms are incompletely understood. To further characterize the pathological phenotype we performed RNA sequencing of mesenchymal stromal cells from patients with myelodysplastic syndromes and acute myeloid leukemia and found a specific molecular signature of genes commonly deregulated in these disorders. Pathway analysis showed a strong enrichment of genes related to osteogenesis, senescence, inflammation and inhibitory cytokines, thereby reflecting the structural and functional deficits of mesenchymal stromal cells in myelodysplastic syndromes and acute myeloid leukemia on a molecular level. Further analysis identified transforming growth factor β1 as the most probable extrinsic trigger factor for this altered gene expression. Following exposure to transforming growth factor β1, healthy mesenchymal stromal cells developed functional deficits and adopted a phenotype reminiscent of that observed in patient-derived stromal cells. These suppressive effects of transforming growth factor β1 on stromal cell functionality were abrogated by SD-208, an established inhibitor of transforming growth factor β receptor signaling. Blockade of transforming growth factor β signaling by SD-208 also restored the osteogenic differentiation capacity of patient-derived stromal cells, thus confirming the role of transforming growth factor β1 in the bone marrow microenvironment of patients with myelodysplastic syndromes and acute myeloid leukemia. Our findings establish transforming growth factor β1 as a relevant trigger causing functional inhibition of mesenchymal stromal cells in myelodysplastic syndromes and acute myeloid leukemia and identify SD-208 as a candidate to revert these effects.